CRISIS-DRIVEN DIGITAL TRANSFORMATION: A MULTIVARIATE ANALYSIS OF OTT PLATFORM ADOPTION AND CONSUMER BEHAVIOR IN INDIA DURING COVID-19 (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
This study investigates the transformative impact of the COVID-19 pandemic on Over The-Top (OTT) platform adoption and consumer behaviour in India, focusing on the migration from traditional entertainment media to digital streaming services during crisis conditions. A cross-sectional survey was conducted among 400 Indian consumers aged 18–35 years using stratified sampling across major cities. Data were collected via an online structured questionnaire and analysed using SPSS 29.0 and AMOS, employing descriptive statistics, chi-square tests, correlation analysis, multiple and hierarchical regressions, and structural equation modelling (SEM) to test the proposed relationships. Results indicate a substantial increase in OTT subscriptions during COVID-19, with significant behavioural substitution away from theatres (−74.7%) and increased weekly OTT viewing (+131%). Perceived usefulness, ease of use, and entertainment gratifications significantly predicted behavioural intention, while lockdown duration and income acted as strong contextual moderators (final model R² = 0.69). Findings show that crisis exposure significantly amplified technology acceptance and gratification-driven motives, accelerating OTT adoption. The study extends existing Technology Acceptance and Uses & Gratifications frameworks by examining their joint applicability in a crisis-driven context, providing multivariate empirical validation of OTT adoption in emergent market settings. The study offers managerial insights for segmentation, localization, and post-crisis retention strategies.
Keywords: OTT platforms, Technology Acceptance Model, Uses & Gratifications, crisis behaviour, digital adoption, consumer behaviour, India.